Perilaku Konsumsi Kosmetik Pada Mahasiswi Universitas Darussalam Gontor: Pendekatan Islamisasi Teori Konsumsi - Sa'diah, Zulfatus; May Shinta Retnowati; Rizki Apriliani (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Industrial development in this advanced era can be said to be very rapid, one of which is the cosmetics industry. In fact, many people in this era view that cosmetics are no longer just an additional need, but rather a primary need. As time goes by, a beautiful, enchanting and attractive appearance is every individual's unlimited dream. Cosmetics themselves cannot be separated from a woman's daily life. Female students are one of the social groups most susceptible to the influence of fashion and lifestyle and are one of the largest consumers who use cosmetic products. This research is field research. Research data was obtained using observation, interviews and documentation methods. The data collected was then analyzed using the Islamization of consumption theory approach with descriptive analysis methods. The results obtained are that first, consumption behavior that occurs in terms of the concept of needs and desires is largely not limited by the concept of maslahah. Second, most of them have reflected the concept of goods and services that are limited to halal and have also seen it from the thayyib side, because the goods they buy do not cause harm or harm to them physically or mentally. Third, most of them put cosmetics as part of their hajjiyat needs. Most of them still have a goal limited to satisfaction of use value (utility), but are not yet limited to the concept of maslahah, but there is a small portion of students who view that apart from the benefits they get, they intend this for worship. They see that by taking good and healthy care of their skin, it means they intend to maintain facial cleanliness, which is part of their faith.